Analisis Kemampuan Menyusun Laporan Keuangan, Literasi Keuangan, Inklusi Keuangan terhadap Kinerja Keuangan UMKM - Mayndarto, Eko Cahyo (Jurnal EMT KITA, 2026)
Low financial literacy in utilizing financial applications or limited access to capital illustrates the real conditions of MSMEs in South Jakarta. This study aimed to analyze the ability to prepare financial reports, financial literacy, and financial inclusion on the financial performance of MSMEs in South Jakarta. MSME financial performance is a crucial factor in maintaining business sustainability amidst the competition and dynamics of the urban economy. The research method used a quantitative method to collect data using a questionnaire distributed to MSMEs in South Jakarta. The sample size was 93 respondents. The data were analyzed using multiple linear regression analysis to test the influence of each independent variable on financial performance. The partial results indicate that the ability to prepare financial reports, financial literacy, and financial inclusion have a significant positive influence on MSME financial performance. The Adj. R2 obtained a value of 59.6%. From the results, the ability to prepare financial reports, financial literacy, and financial inclusion simultaneously have a significant positive influence on financial performance. These results indicate that if financial understanding is improved, financial recording and reporting skills, as well as financing for financial services can encourage more effective and sustainable business management.